The potential job opportunities for Halal Science Graduates in education sector in Negara Brunei Darussalam - Deuraseh, Nurdeng; Hashim, Norkhairiah; Raffi, Raihana Mohd; Fikriyah, Noor Rabiatul; Ahmad, Nurul Husna Abu Bakar (Technium Social Sciences Journal, 2022)
A concern for graduates in Brunei Darussalam is the difficulty of finding a stable career after graduation. Although Brunei is considered one of the richest countries in the world with a relatively small population, the unemployment rate keeps increasing, which is a problem for future graduates from various universities in this country. Therefore, this research focuses on studying the potential employment opportunities for Halal Science Graduates specifically in the education sector as it is well known that education plays an important role in enabling people of all ages and religions to engage in quality learning throughout their lives. Education is the process of acquiring knowledge, values, skills, beliefs and moral habits. For this reason, it is absolutely important for people to learn Halal education in order to gain more knowledge about Halal and apply it in their daily lives. The issue here is Halal education is not emphasized enough in primary and secondary education. It should be addressed earlier to lay a foundation of the Halal theory among the potential workforce. As the demand for Halal qualified manpower is increasing, Halal education should be given more significant in general education. Hence, this study seeks opportunities for Halal Science Graduates, to make a career in the education sector by conducting a survey on people’s opinion about Halal education. In this study, it is found that many people agree with studying halal education from an early age or starting it in primary education. Moreover, majority of the respondents preferred a teacher from Halal Science Graduates with Master of Teaching to teach them about Halal.